From austerity to necropolitics in pandemic times, European style - Tulumello, Simone (2020)
With a global pandemic putting into crisis health systems, like the Italian, among the strongest in the world, while draconian measures destined to wipe out entire sectors of the economies are put in place in the name of defending the populations that are vulnerable to Covid-19, socialising debt has become, right within Europe, a matter of life and death. New and old cleavages articulate to determine the bodies that are expendable or not: age, health conditions, class, but also each country’s capacity to shut down its economy the longer or to buy ventilators. Fortress Europe shattered up in a fragmentation of bodies with different right to live.